O długim trwaniu, czyli o kilku dworach z terenu Sieradzkiego - Kajzer, Leszek (Zeszyty Wiejskie, 2016)
The focus of this article are medieval and modern manor houses from the area of the Sieradz Land, which is a historical region in the central Poland. For the author the “manor houses” are not only the buildings, but also an important manifestation of the long-term historical processes – the tradition of locating the manor house in the center of a large property. Forms of the manor houses changed through the centuries. The latemedieval “fortified manors” were often built as towers on the moated earthen mounds. In modern times, comfort became more important than safety. These architectural changes reflect also the transformation of the medieval chivalry in the landed gentry. In article 12 towns and villages are analyzed. Thanks to the researches of historians and archaeologists the transformation of manor houses can be observed from the breakthrough of the13th to the 14th century until the breakthrough of the 19th to the 20th. The author believes that the research on the gradual transformation of the manor buildings, from the chivalry fortified house to the comfortable seats of gentry, is more interesting than focusing on the analysis of the monument preserved to this day, which is the last one in the series of described transformations.